Anticipated Regret, Entrepreneurial Cognition, and Entrepreneurial Persistence - Mei-jiao Huang; Mei-jiao Huang; Zhong-bin Li; Xiao-feng Su (Frontiers in Psychology, 2022)
Based on the regret regulation theory and entrepreneurial cognition theory, this study aims to investigate the relationship between entrepreneurs’ anticipated regret and entrepreneurial persistence through the mediator of entrepreneurial cognition. To that end, we distributed surveys to entrepreneurs who were supported by the “Xing Chuang Tian Di” project and used 248 questionnaire data to examine the hypotheses. The results show that entrepreneurs’ anticipated regret has a significant and direct impact on entrepreneurial persistence. Also, entrepreneurship cognition plays a mediating role between anticipated regret and entrepreneurial persistence. In addition, the entrepreneurial environment plays a positive role in moderating the relationship between anticipated regret and entrepreneurial persistence.